2022
DOI: 10.3390/ijms23147793
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin Receptor: An Important Target for the Development of Novel Medicines and Pesticides

Abstract: The insulin receptor (IR) is a transmembrane protein that is activated by ligands in insulin signaling pathways. The IR has been considered as a novel therapeutic target for clinical intervention, considering the overexpression of its protein and A-isoform in multiple cancers, Alzheimer’s disease, and Type 2 diabetes mellitus in humans. Meanwhile, it may also serve as a potential target in pest management due to its multiple physiological influences in insects. In this review, we provide an overview of the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 282 publications
0
10
0
Order By: Relevance
“…We thus propose that the combination of chemotherapy with INSR inhibitors and NAMPT inhibitors could represent a promising treatment strategy for early chemoresistant HGSOC patients. The inhibitors of NAMPT and INSR have undergone extensive development and clinical testing (58,59). Previous research has demonstrated that the combination of a NAMPT inhibitor and chemotherapy resulted in a better prognosis than chemotherapy alone in mice with HGSOC (60), holds promise for further improving the therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…We thus propose that the combination of chemotherapy with INSR inhibitors and NAMPT inhibitors could represent a promising treatment strategy for early chemoresistant HGSOC patients. The inhibitors of NAMPT and INSR have undergone extensive development and clinical testing (58,59). Previous research has demonstrated that the combination of a NAMPT inhibitor and chemotherapy resulted in a better prognosis than chemotherapy alone in mice with HGSOC (60), holds promise for further improving the therapeutic window.…”
Section: Discussionmentioning
confidence: 99%
“…There are several upstream signalling events in GLUT4 translocation stimulated by insulin binding to its receptor on the membrane of target cells [ 36 ]. The extracellular α subunit of the insulin receptor undergoes a conformational change upon binding with insulin, leading to the facilitation of ATP binding to the β subunit of the receptor [ 52 ]. This triggers the phosphorylation of intracellular substrate proteins and insulin-responsive substrates (IRSs) and further mediates insulin-mediated downstream signalling events, leading to GLUT4 movement and glucose uptake (as depicted in Figure 1 ) [ 53 ].…”
Section: Glucose Metabolismmentioning
confidence: 99%
“…Briefly, the insulin/insulin receptor signaling cascade consists of two main branches emanating from the insulin receptor-insulin receptor substrate (IRS) node: the phosphatidylinositol 3-kinase (PI3K, a lipid kinase)/AKT (also known as PKB or protein kinase B) pathway and the Raf/Ras/MEK/MAPK (mitogen activated protein kinase, also known as ERK or extracellular signal regulated kinase) pathway [ 136 , 137 , 138 ]. After phosphorylation on tyrosine residues in their C-termini, IRS adaptor proteins serve as docking sites for the recruitment of downstream signaling effectors [ 139 , 140 ]. What may be relevant in PCOS is that the coexistence of inflammatory signaling via the NF-κB and activator protein 1 (AP-1)/c-Fos/c-Jun pathways results in the activation of serine kinases, I-kappa-B-kinase beta (IKKβ) and c-Jun N-terminal kinase 1 (JNK1), with a subsequent reduction in IRS signaling ability.…”
Section: Epigenetic Regulation Of Insulin Resistance and Inflammatory...mentioning
confidence: 99%